The Implementation of the Al-Qur'an Memorization Program at the Palembang Alumnika Science Elementary School - Febriyanti Febriyanti; Afif Alfiyanto; Zulkipli Zulkipli; Bitri Ayuni (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2022)
The substance of this research is implementing the Al-Qur'an memorization program by involving leaders of educational institutions, teachers, students, and parents. This study seeks to determine the process of implementing the Al-Qur'an memorization program at the Palembang Sains Alumnika Elementary School and the supporting and inhibiting factors. The research used a qualitative method with a descriptive approach. The informants were the principal, the head of the program, and the teacher memorizing the Qur'an. Data collection techniques were used interviews, observation, and documentation. Data analysis techniques through data condensation, data presentation, and concluding. This study indicated that the implementation of the Al-Qur'an memorization program could be seen from 1) organizing, namely a) making an organizational structure; b) classifying teachers; and c) grouping students; 2) direction, which is given at the beginning of each new academic year; 3) motivation; and 4) coordination, namely holding a meeting at the beginning of each semester. The supporting factors, namely 1) the existence of motivation; 2) the age of students who are still children; 3) the availability of teachers to memorize; 4) there is support from the school environment and parents of students. While the inhibiting factors, namely 1) some students have not been able to read the Qur'an fluently; and 2) students are less routine in repeating memorization because of online learning.